Validade de métodos de diagnóstico da lesão de cárie oclusal incipiente em dentes permanentes. estudo in vitro. - Mota, Luciane de Queiroz (2002)
The diagnosis of initial occlusal caries is a very difficult procedure which can result in differences among dental professionals evaluation. The purpose of this research work is to investigate the validity of visual inspection, bitewing radiograph and the use of a dye in the diagnosis of initial occlusal carie in 50 permanent posterior teeth and it s reproducibility. The exams were conducted by three professionals and a histological analyses of the sites served as the gold standard to validate the data. The visual inspection presented larger sensitivity value (56,3%) than the bitewing radiograph (4,6%) and the dye technique (29,9%), while the specificity values were 85,4%, 100% e 87,8% respectively. The interexaminer reproducibility was in the range of 62,5% to 92,9%, while the intraexaminer reproducibility standed between 63,9% to 95,4%. The visual inspection can be considered as an important method of diagnosis of initial occlusal caries, however, it depends on the knowledge about caries evolution, as well as on the caries diagnostic criteria well defined, which also influences the reprodutibility values.